Dose and age dependent effects of lactate supplementation in shaping gut microbiota - Futing Luo; Tao Shao; Xiangdong Liu; Qiyuan Yang; Yang Gai; Guiling Ma; Yanting Chen (Journal of Functional Foods)
Effects of lactate supplementation on gut microbiota composition included profound inconsistency, leaving significant gaps in understanding its impacts on gut microbiome. This study investigated the effects of lactate supplementation on gut microbiota composition, focusing on age-dependent responses. A meta-analysis of 217 datasets (5,359 subjects) evaluated lactate’s impact on core microbiota. Results showed that lactate supplementation significantly increased beneficial bacteria, such as Lactobacillus and Bifidobacterium, with consistent effects in young adults, while older adults showed more variability. Lactate also decreased the Firmicutes-to-Bacteroidetes ratio, indicating potential gut function improvements. Pathogen abundance, including Bacteroides, was unaffected. Regression analysis revealed a linear increase in Lactobacillus abundance with doses exceeding 2,000 mg/day, while Bifidobacterium increased at doses between 10 and 5,500 mg/day. Clostridium abundance was significantly reduced at doses above 3,000 mg/day. These findings highlight the dose- and age-dependent benefits of lactate supplementation on gut microbiota and overall gut health.